Relayout of Production Layout to Reduce Material Handling Costs - Firmansyah, Mochamad Jordan Dwi; Putri, Erni Puspanantasari (Journal La Multiapp, 2025)
Despite its long-standing operation, the company faces several issues related to the production floor layout, such as inefficient material flow, high waiting times, and suboptimal space utilization. These problems have led to decreased productivity, time inefficiencies, and an uncomfortable work environment. This study aims to redesign the production floor layout using the Systematic Layout Planning (SLP) method to improve material flow efficiency and productivity. The SLP method helps identify the relationships between activities and design an optimal layout by minimizing material transfer distances, reducing waiting times, and creating a more comfortable workspace. The research results are expected to provide optimal solutions for maximizing the efficiency of material handling distance and time while demonstrating the positive impact of layout changes on material handling costs. This study successfully redesigned the production facility layout to enhance operational efficiency. Changes were made to facilities C, D2, P, G, J, and I, along with the relocation of machine K and the removal of cutting machine H, which was no longer in use. The results showed a significant reduction in material transfer distances, from 23,457.5 meters to 13,194.65 meters per month (a 43.9% reduction). Additionally, material transfer times decreased from 438.41 minutes to 298.23 minutes per month (a 31.98% reduction). A comparison between the initial and proposed layouts revealed a reduction in material handling costs from IDR 269,738 to IDR 206,452 per month, resulting in savings of 23.46%. The layout optimization proved effective in reducing material flow inefficiencies, directly impacting operational cost reduction and productivity improvement.